Repliker ur det förflutna - Wallin, Eva (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
In this article I analyze role-takings in a life history narrative where manifestations of the narrator emanating from different time segments interact with several actors from different periods of her life. In the epic flow of the narration, quotations from such characters suddenly broke in as dramatic reminders of the original events, where the narrator entered the parts of persons she had met earlier in her life. When isolated from the rest of the conversation, it became obvious that these lines from the past constituted a narrative of their own, a dramatic "grand narrative" of the narrator’s experience of a lengthy illness period.